Handling of radioactive seed localisation breast specimens in the histopathology laboratory. Issue 1 (January 2015) - Dessauvagie, B. F.; Frost, F. A.; Sterrett, G. F.; Hardie, M.; Parry, J.; Latham, B.; Westcott, E.; Rourke, T.; Burrage, J.; Bourke, A.; Taylor, D.; Kamyab, R.; et al.
<x xml:space="preserve">Abstract</x> Summary Radio-guided occult lesion localisation using iodine-125 seeds (ROLLIS) is a novel method of localisation for impalpable in situ and invasive carcinomas that has been the subject of a recent pilot study and pilot study extension in Western Australia. Robust protocols for radiation safety, specimen labelling, specimen tracking, seed retrieval and seed disposal were developed at two Western Australian laboratories to minimise the risk of seed loss. The processes are safe and effective with no significant radiation exposure to pathologists and with acquisition of all seeds intact and undamaged. The success can be attributed to developing specific seed retrieval techniques, suited to local preferences at each institution, with input from surgeons, radiologists and medical physics personnel. These techniques are now routine and will continue in the randomised control phase of the ROLLIS study.